Savage salvation [videorecording (DVD)] - Barker, Adam Taylor; Sivertson, Chris; Huston, Jack, 1982-; De Niro, Robert; Fitzgerald, Willa; Malkovich, John (Vertical, 2023)
After his fiancé dies of an overdose, a recovering addict embarks on a vengeful killing spree, hunting down the drug dealers before the town sheriff puts an end to his vigilante justice.